Rescue procedure for isolated dystonia after the secondary failure of globus pallidus internus deep brain stimulation - Lin, Suzhen; Wang, Lingbing; Shu, Yimei; Guo, Shunyu; Wang, Tao; Li, Hongxia; Zhang, Chencheng; Sun, Bomin; Li, Dianyou; Wu, Yiwen (Frontiers in Neuroscience, 2022)
Introduction: Globus pallidus internus (GPi) deep brain stimulation (DBS) is widely used in patients with dystonia. However, 10-20% of patients receive insufficient benefit. The objectives of this study are to evaluate the effectiveness of bilateral subthalamic nucleus (STN) DBS along with unilateral posteroventral pallidotomy (PVP) in patients with dystonia who experienced unsatisfactory GPi-DBS and to address the reported rescue procedures after suboptimal DBS or lesion surgery in dystonia patients. Methods: Six patients with isolated dystonia who had previously undergone bilateral GPi-DBS with suboptimal improvement were included. Standardized assessments of dystonia using Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) and quality of life using SF-36 were evaluated before surgery and 1, 6 months and last follow up (LFU) after surgery. STN bilateral OFF (bi-OFF), unilateral ON (uni-ON) and bilateral ON (bi-ON) states were recorded at LFU. Specific items were used to find publications published before April 10, 2022 regarding rescue procedures after suboptimal DBS or lesion surgery in patients with dystonia for reference. Eleven original studies including case reports/series were identified for discussion. Results: Substantial clinical benefits were achieved in all six patients. Significant amelioration was achieved during the 1-month (6.5±7.45; p= 0.0049), 6-month (5.67±6.3; p= 0.0056) follow-ups, and at LFU (4.67±4.72; p= 0.0094) when compared with the baseline (LFU of GPi DBS with on status) (17.33±11.79) assessed by BFMDRS. The percentage of improvement reached 70.6%, 74.67%, and 77.05%, respectively. At LFU, significant differences were found between the stimulation bi-OFF and uni-ON (11.08±8.38 vs 9±8.52, p= 0.0191), and between the stimulation bi-OFF and bi-ON (11.08±8.38 vs 4.67±4.72, p= 0.0164). Trends depicting a better improvement in stimulation bi-ON compared with uni-ON (4.67±4.72 vs 9±8.52, p = 0.0538) were observed. Conclusions: Our results suggest that bilateral STN-DBS plus unilateral PVP may be an effective rescue procedure for patients with isolated dystonia who experienced suboptimal movement improvement following GPi-DBS. However, given the heterogeneity of patients and the small sample size, these findings should be interpreted with caution.